Subsequently Direct Right Maximum Minimum Financial plan Eventual Procedure for Sheltered and Fanatical Rectangular Arrangement - et. al., K. Thiagarajan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research, the proposed algorithm is Next Immediate Right Maximum Minimum Allotment method. This algorithm is to calculate the optimal value of cost for the Travelling agent to reduce the transportation cost. The expressed algorithm is very useful to derive the allotment in every sector of the rectangular matrix without any disturbance in degeneracy condition.